1998
DOI: 10.1002/(sici)1097-4636(199804)40:1<1::aid-jbm1>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Bone response to unloaded and loaded titanium implants with a sandblasted and acid-etched surface: A histometric study in the canine mandible

Abstract: Many dental clinical implant studies have focused on the success of endosseous implants with a variety of surface characteristics. Most of the surface alterations have been aimed at achieving greater bone-to-implant contact as determined histometrically at the light microscopic level. A previous investigation in non-oral bone under short-term healing periods (3 and 6 weeks) indicated that a sandblasted and acid-etched titanium (SLA) implant had a greater bone-to-implant contact than did a comparably-shaped imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
426
2
23

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 601 publications
(467 citation statements)
references
References 18 publications
16
426
2
23
Order By: Relevance
“…The surface roughness of titanium implants affects the rate of osseointegration and biomechanical fixation [10,20]. Several in vitro studies have reported the effects of surface roughness on the adhesion, proliferation, and differentiation of osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The surface roughness of titanium implants affects the rate of osseointegration and biomechanical fixation [10,20]. Several in vitro studies have reported the effects of surface roughness on the adhesion, proliferation, and differentiation of osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Structures of nano-meter level can form on the surface of implants by immersion in hot solutions of strong acids (hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid) 32) . Roughness of nano-meter level has known to synergistically promote osteogenic proliferation and differentiation, and bone formation 8) . In this study, we confirmed that the same modification of the surface topography for dental implants was properly performed on Cp-Ti samples, and fatigue property was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of shot blasting and acid etching is often performed on Cp-Ti implants because it reportedly accelerates osseointegration [8][9][10][11][12][13][14][15] . In vitro experiments have demonstrated that the combination promotes adhesion, proliferation, and differentiation of osteoblasts [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to decrease this clinical problem is to use a dental implant with a treated surface. It has been suggested that physiochemical and dielectric properties, crystal structure and surface morphology of titanium oxide films on dental implant surfaces play a crucial role in the biocompatibility and osseointegration of implants [3][4][5]. Consequently, numerous modifications for dental implants have been proposed and carried out to improve surface quality and to obtain the most biocompatible implant surface.…”
Section: Introductionmentioning
confidence: 99%